Fluorescent metal organic framework / cellulose nanocrystal composite material as well as preparation method and application thereof

The fluorescent metal organic frame/cellulose nanocrystal composite material prepared by solvothermal reaction solves the problem of poor dispersion of AIE-MOF in water, achieves high sensitivity sensing performance, and is suitable for lactic acid detection in aqueous media and other applications.

CN119391192APending Publication Date: 2025-02-07JINAN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411495566.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing aggregation-induced luminescent metal organic framework materials (AIE-MOFs) have poor dispersion in water, resulting in few active sites and low sensing sensitivity.

Method used

Fluorescent metal organic frame/cellulose nanocrystals composite material was prepared by mixing the suspension of zinc acetate, tetracarboxyphenyl ethylene and cellulose nanocrystals (CNCs) and undergoing a solvothermal reaction. This method utilizes the high specific surface area and hydrophilic properties of CNCs to improve the dispersion of the material in water, and optimizes the morphology and sensing properties of the material by controlling the mass ratio and reaction conditions.

Benefits of technology

The prepared fluorescent metal organic frame/cellulose nanocrystal composite has good dispersion in water and excellent sensing sensitivity, which is suitable for detecting substances such as lactic acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391192A_ABST
    Figure CN119391192A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aggregation-induced emission materials, and particularly relates to a fluorescent metal organic framework / cellulose nanocrystal composite material as well as a preparation method and application thereof. The preparation method of the fluorescent metal organic framework / cellulose nanocrystal composite material comprises the following steps: mixing a zinc acetate solution, a tetra (4-carboxybenzene) ethylene solution, nitric acid and a suspension of CNCs, and carrying out solvothermal reaction to obtain the fluorescent metal organic framework / cellulose nanocrystal composite material, the mass ratio of the zinc acetate to the tetrakis (4-carboxybenzene) ethylene to the CNCs is (10-100): (5-100); the mass ratio of the tetra (4-carboxybenzene) ethylene to the CNCs is (5-20): (0.1-5). The fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the preparation method provided by the invention is good in dispersity in water, has an aggregation-induced emission effect and is excellent in sensing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aggregation-induced luminescence materials, and specifically relates to a fluorescent metal organic framework / cellulose nanocrystal composite material and a preparation method and application thereof. Background Art

[0002] Metal-Organic Framework (MOF) has a periodic network structure formed by metal ions or metal clusters and organic ligands through coordination bonds. Thanks to its highly developed pore structure and flexibly regulated physical and chemical properties, MOF is gradually becoming one of the important research directions of sensing materials.

[0003] Aggregation-induced emission (AIE) refers to the enhancement of fluorescence emission signals when the movement of groups within a molecule is restricted, and the decrease of fluorescence intensity when the group is dispersed. Aggregation-induced emission MOF (AIE-MOF) activates the fluorescence switching properties of AIE groups by means of framework immobilization, providing a new opportunity for the development of sensing materials. However, AIE-MOF currently has poor dispersibility in water, resulting in fewer active sites. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a fluorescent metal organic framework / cellulose nanocrystal composite material and its preparation method and application. The fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the preparation method provided by the present invention has good dispersibility in water and excellent sensing sensitivity.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a fluorescent metal organic framework / cellulose nanocrystal composite material, comprising the following steps:

[0007] A zinc acetate solution, a tetra(4-carboxyphenyl)ethylene solution, nitric acid and a CNCs suspension are mixed and subjected to a solvothermal reaction to obtain a fluorescent metal organic framework / cellulose nanocrystal composite material;

[0008] The mass ratio of zinc acetate to tetra(4-carboxyphenyl)ethylene and CNCs is (10-100):(5-100); the mass ratio of tetra(4-carboxyphenyl)ethylene to CNCs is (5-20):(0.1-5).

[0009] Preferably, the concentration of the CNCs suspension is 1 to 10 wt.%.

[0010] Preferably, the mass ratio of zinc acetate to the volume ratio of the solvent in the zinc acetate solution is (10-100) mg: (1-15) mL; the mass ratio of tetrakis(4-carboxystyrene)ethylene to the volume ratio of the solvent in the tetrakis(4-carboxystyrene)ethylene solution is (5-100) mg: (1-15) mL.

[0011] Preferably, the temperature of the solvent thermal reaction is 50 to 120° C., and the insulation time is 12 to 72 hours.

[0012] The present invention also provides a fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the above-mentioned preparation method, wherein the aspect ratio of the fluorescent metal organic framework / cellulose nanocrystal composite material is (15-100):1; the fluorescent metal organic framework / cellulose nanocrystal composite material comprises cellulose nanocrystals and MOF supported on the cellulose nanocrystals; the metal atom of the MOF is Zn, and the ligand is tetra(4-carboxyphenyl)ethylene.

[0013] Preferably, the morphology of the fluorescent metal organic framework / cellulose nanocrystal composite material is "needle-like clusters" or "petal clusters".

[0014] The present invention also provides a fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the above-mentioned preparation method or the use of the above-mentioned fluorescent metal organic framework / cellulose nanocrystal composite material in detecting lactic acid.

[0015] The present invention also provides a method for detecting lactic acid using the fluorescent metal organic framework / cellulose nanocrystal composite material described in the above technical solution, comprising the following steps:

[0016] Test the initial fluorescence intensity F0 of the fluorescent metal organic framework / cellulose nanocrystal composite solution;

[0017] After mixing the test solution containing lactic acid and the fluorescent metal organic framework / cellulose nanocrystal composite material solution, the fluorescence intensity is tested to obtain the fluorescence intensity F of the test solution;

[0018] Obtaining the concentration of lactic acid in the test solution containing lactic acid according to a predetermined linear curve, the initial fluorescence intensity F0 and the ratio F / F0 of the fluorescence intensity F;

[0019] The predetermined linear curve is F 标准 Linear relationship curve between / F0 and lactate concentration;

[0020] The F 标准 To test the fluorescence intensity of fluorescent metal organic framework / cellulose nanocrystal composite solutions containing different concentrations of lactic acid.

[0021] The present invention also provides a paper sensor, comprising a paper substrate and a fluorescent metal organic framework / cellulose nanocrystal composite material loaded in the paper substrate; the fluorescent metal organic framework / cellulose nanocrystal composite material is the fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the above-mentioned preparation method or the above-mentioned fluorescent metal organic framework / cellulose nanocrystal composite material.

[0022] Preferably, the fluorescent metal organic framework / cellulose nanocrystal composite material is 2 The loading capacity of the paper matrix is ​​5×10 -6 ~1×10 -3 mg.

[0023] The present invention provides a method for preparing a fluorescent metal organic framework / cellulose nanocrystal composite material, comprising the following steps: mixing a zinc acetate solution, a tetra(4-carboxyphenyl)ethylene solution, nitric acid and a suspension of CNCs, and performing a solvothermal reaction to obtain a fluorescent metal organic framework / cellulose nanocrystal composite material; the mass ratio of the zinc acetate to the tetra(4-carboxyphenyl)ethylene and the CNCs is (10-100):(5-100); the mass ratio of the tetra(4-carboxyphenyl)ethylene to the CNCs is (5-20):(0.1-5). The present invention in-situ grows AIE-MOF on CNCs, on the one hand, utilizing the high specific surface area and surface chemical activity of CNCs to provide abundant active sites for the uniform dispersion of AIE-MOF, thereby promoting the improvement of the sensing performance of the composite material; on the other hand, the hydrophilic properties of CNCs will also promote the dispersion of the fluorescent metal organic framework / cellulose nanocrystal composite material in an aqueous medium. In addition, the present invention controls the mass ratio of zinc acetate, tetra(4-carboxyphenyl)ethylene and CNCs within the above range, which can limit the morphology of the final fluorescent metal organic framework / cellulose nanocrystal composite material. Within this range, the final product component units are nanorod-shaped or nanosheet-shaped, and the structure has a high aspect ratio, which can further promote the improvement of sensing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 SEM image of MOF@CNCs-1;

[0025] Figure 2 SEM image of MOF@CNCs-2;

[0026] Figure 3 SEM image of MOF@CNCs-2;

[0027] Figure 4 Microscopic fluorescence photos of MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3 irradiated with 365nm laser;

[0028] Figure 5 The predetermined standard curves of MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3;

[0029] Figure 6 The optical image and CIE chromaticity diagram of the MOF@CNCs-1 suspension after adding different concentrations of lactic acid solution to the MOF@CNCs-1 suspension under 365nm ultraviolet light excitation;

[0030] Figure 7 The results of the AIEgen-based two-dimensional MOF sensing test obtained by MOF@CNCs-1 and the comparative example;

[0031] Figure 8 is the standard curve of G value and lactic acid concentration. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a fluorescent metal organic framework / cellulose nanocrystal composite material, comprising the following steps:

[0033] A zinc acetate solution, a tetra(4-carboxyphenyl)ethylene solution, nitric acid and a CNCs suspension are mixed and subjected to a solvothermal reaction to obtain a fluorescent metal organic framework / cellulose nanocrystal composite material;

[0034] The mass ratio of zinc acetate to tetra(4-carboxyphenyl)ethylene and CNCs is (10-100):(5-100); the mass ratio of tetra(4-carboxyphenyl)ethylene to CNCs is (5-20):(0.1-5).

[0035] The invention mixes a zinc acetate solution, a tetra(4-carboxyphenyl)ethylene solution, nitric acid and a CNCs suspension, and performs a solvent thermal reaction to obtain a fluorescent metal organic framework / cellulose nanocrystal composite material.

[0036] As an embodiment, the mass ratio of zinc acetate (Zn(CH3COO)2) and tetrakis(4-carboxystyrene)ethylene (H4TCPE) is (10-100):(5-100); in a specific embodiment, the mass ratio of Zn(CH3COO)2 and H4TCPE can be 30:10.

[0037] As an implementation mode, the mass ratio of H4TCPE and CNCs is (5-20):(0.1-5); in a specific embodiment, the mass ratio of H4TCPE and CNCs can be 12.5:1, 4.17:1, or 2.5:1.

[0038] As an embodiment, the solvent in the Zn(CH3COO)2 solution is one or more of N,N-diethylformamide (DEF), N,N-dimethylformamide (DMF), tetrahydrofuran and dimethyl sulfoxide (DMSO). In a specific embodiment, the solvent can be DEF. As an embodiment, the mass ratio of Zn(CH3COO)2 to the volume ratio of the solvent in the Zn(CH3COO)2 solution is (10-100) mg: (1-15) mL. In a specific embodiment, the mass ratio of Zn(CH3COO)2 to the volume ratio of the solvent in the Zn(CH3COO)2 solution is 30 mg: 3 mL.

[0039] As an embodiment, the solvent in the H4TCPE solution is one or more of methanol, ethanol, n-butanol and isopropanol, and in a specific embodiment, it can be ethanol. As an embodiment, the mass ratio of H4TCPE to the volume ratio of the solvent in the H4TCPE solution is (5-100) mg: (1-15) mL, and in a specific embodiment, the mass ratio of H4TCPE to the volume ratio of the solvent in the H4TCPE solution is 10 mg: 3 mL.

[0040] As an embodiment, the mixing is: firstly, a solution of Zn(CH3COO)2 is mixed with a solution of H4TCPE to obtain a suspension; after nitric acid is added dropwise to the suspension, a second mixing is performed with the suspension of CNCs.

[0041] As an embodiment, the Zn(CH3COO)2 solution and the H4TCPE solution are mixed by ultrasonication in a water bath, and the ultrasonication time is 10 minutes.

[0042] As an embodiment, the concentration of the nitric acid is 10-100%, and in a specific embodiment, the concentration of the nitric acid can be 65-68%. As an embodiment, the volume ratio of the Zn(CH3COO)2 solution to the nitric acid is 1-10mL:1-100μL, and in a specific embodiment, the volume ratio of the Zn(CH3COO)2 solution to the nitric acid can be 3mL:40μL. As an embodiment, the dripping speed is 1-50 drops / min.

[0043] As an embodiment, the second mixing method is stirring, the stirring temperature is room temperature, the stirring speed is 200-1000 rpm, and the time is 5-40 min. In a specific embodiment, the stirring speed can be 800 rpm and the time can be 30 min.

[0044] As an implementation mode, the temperature of the solvent thermal reaction is 50-120° C., and the insulation time is 12-72 hours. In a specific embodiment, the temperature of the solvent thermal reaction can be 80° C., and the insulation time can be 48 hours.

[0045] During the above solvothermal reaction process, CNCs act as structural templates to guide the assembly and crystallization of metal-organic frameworks.

[0046] As an embodiment, after the solvothermal reaction, the solid phase obtained by the solvothermal reaction is further washed, and the washing includes DMF washing, ethanol washing and water washing performed in sequence. As an embodiment, the washing is performed until neutral.

[0047] The present invention also provides a fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the preparation method described in the above technical solution.

[0048] As an implementation manner, the aspect ratio of the fluorescent metal organic framework / cellulose nanocrystal composite material is 15 to 100:1. In a specific embodiment, the aspect ratio can be 80.1:1.

[0049] As an embodiment, the fluorescent metal organic framework / cellulose nanocrystal composite material includes cellulose nanocrystals and MOF supported on the cellulose nanocrystals; the metal atom of the MOF is Zn, and the ligand is tetra(4-carboxyphenyl)ethylene; the morphology of the fluorescent metal organic framework / cellulose nanocrystal composite material is "needle-like clusters" or "petal clusters".

[0050] In the present invention, the introduction of CNCs has the following advantages:

[0051] The high specific surface area and surface chemical activity of CNCs provide abundant active sites for the uniform dispersion of AIE-MOF, thereby enhancing the overall performance of the composite. For example: (1) The excellent mechanical properties of CNCs enhance the mechanical stability of the composite, while their biocompatibility and renewability provide potential advantages for the composite in biomedical and environmental protection applications. For example, the mechanical properties are improved, and the strength and flexibility of the composite are optimized, making it more suitable for applications in flexible electronics and wearable devices. The improvement of biocompatibility opens up new possibilities for biomedical applications such as drug carriers and tissue engineering.

[0052] (2) CNCs are easy to chemically modify, making it possible to regulate the functionality of the material and promoting the photophysical properties of AIE-MOF in composite materials, such as fluorescence enhancement and photostability. In addition, the introduction of CNCs enhances the responsiveness of the material to environmental changes, improves the UV shielding ability, and improves the processability of the material, expanding its application range in multiple fields.

[0053] In terms of catalytic performance, morphology regulation optimizes the accessibility of catalytic active sites, which is crucial for catalytic applications. At the same time, composite materials with specific morphologies exhibit more effective UV absorption and scattering capabilities, providing a new direction for the development of new UV shielding materials.

[0054] (3) By controlling the content of CNCs in the composite material, the morphology of the composite material is changed to optimize the fluorescence emission intensity and light scattering properties, which is crucial for the development of sensors and optical devices. In addition, morphological diversity also improves the adsorption and separation efficiency, providing a structural basis for gas adsorption, separation and storage. Environmental responsiveness is also enhanced by specific morphology, making the material more sensitive to changes in humidity and temperature, providing a new way for the development of smart materials and sensors.

[0055] The present invention also provides a method for detecting lactic acid using the fluorescent metal organic framework / cellulose nanocrystal composite material described in the above technical solution, comprising the following steps:

[0056] Test the initial fluorescence intensity F0 of the fluorescent metal organic framework / cellulose nanocrystal composite solution;

[0057] After mixing the test solution containing lactic acid and the fluorescent metal organic framework / cellulose nanocrystal composite material solution, the fluorescence intensity is tested to obtain the fluorescence intensity F of the test solution;

[0058] Obtaining the concentration of lactic acid in the test solution containing lactic acid according to a predetermined linear curve, the initial fluorescence intensity F0 and the ratio F / F0 of the fluorescence intensity F;

[0059] The predetermined linear curve is F 标准 Linear relationship curve between / F0 and lactate concentration;

[0060] The F 标准 To test the fluorescence intensity of fluorescent metal organic framework / cellulose nanocrystal composite solutions containing different concentrations of lactic acid.

[0061] The present invention also provides a paper sensor, comprising a paper substrate and a fluorescent metal organic framework / cellulose nanocrystal composite material loaded in the paper substrate.

[0062] As an embodiment, the fluorescent metal organic framework / cellulose nanocrystal composite material is relative to 1 cm 2 The loading capacity of the paper matrix is ​​5×10 -6 ~1×10 -3 mg.

[0063] As an embodiment, the paper substrate is filter paper.

[0064] The present invention also provides a method for preparing the above-mentioned paper sensor, comprising the following steps:

[0065] The paper sensor is obtained by dropping a suspension of the fluorescent metal organic framework / cellulose nanocrystal composite material onto a paper substrate and then drying the substrate.

[0066] As an embodiment, the drying is natural drying at room temperature, and the drying time is 24 hours.

[0067] As an embodiment, the concentration of the suspension of the fluorescent metal organic framework / cellulose nanocrystal composite material is 1 to 20 mg / L;

[0068] As an implementation method, 1 cm 2 The amount of the suspension of the fluorescent metal organic framework / cellulose nanocrystal composite material added to the paper substrate is 5 to 50 μL.

[0069] The present invention also provides a method for detecting lactic acid using the above-mentioned paper sensor, comprising the following steps:

[0070] Lactic acid of a series of concentrations is dripped onto the paper sensor, and the G values ​​of lactic acid of different concentrations are obtained respectively; the G value is taken as the ordinate and the lactic acid concentration is taken as the abscissa, and a standard curve is obtained by fitting;

[0071] Add lactic acid of unknown concentration to the paper sensor and obtain the G value. According to the G value and the standard curve, the concentration of lactic acid is obtained.

[0072] The fluorescent color of the test paper was photographed using a smartphone under a 365nm UV light, and the G value was extracted in Photoshop.

[0073] Figure 8 is the standard curve of G value and lactic acid concentration, from Figure 8 It can be seen that the standard curve is: y = 1.796x + 129.9, r 2 =1.796.

[0074] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0075] Example 1

[0076] Dissolve 30 mg Zn(CH3COO)2 in 3 mL EDFE to obtain a Zn(CH3COO)2 solution; dissolve 10 mg H4TCPE in 3 mL ethanol to obtain a H4TCPE solution;

[0077] The Zn(CH3COO)2 solution and the H4TCPE solution were ultrasonicated in a water bath for 10 min to form a uniform suspension, and then 40 μL of 65 wt.% nitric acid was added to the suspension under magnetic stirring to obtain a mixed solution. Subsequently, 200 μL of 4 wt.% CNCs suspension was added to the mixed solution, stirred at room temperature for another 15 min, and heated at 80 ° C for 24 h. The solid phase obtained by the reaction was washed with DMF, ethanol and water in sequence until neutral to obtain MOF@CNCs-1.

[0078] Example 2

[0079] The only difference from Example 1 is that the amount of CNCs suspension added is 600 μL, and MOF@CNCs-2 is obtained.

[0080] Example 3

[0081] The only difference from Example 1 is that the amount of CNCs suspension added is 1000 μL, and MOF@CNCs-3 is obtained.

[0082] Take out MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3, transfer them to a clean silicon wafer, and dry them at room temperature 25°C overnight. Then, turn on the scanning electron microscope at a voltage of 20KV and use secondary electron emission to conduct microscopic observation in a high vacuum environment to obtain optical fiber photos of the MOF@CNCs structure. Figures 1 to 3 SEM images of MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3, respectively. Figures 1 to 3 It can be seen that: as the CNCs content gradually increases, there are significant morphological changes among MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3. As the CNCs content increases, the crystal component units of MOF@CNCs change from needle-shaped to rod-shaped, and finally evolve into a flake structure similar to a flower cluster. The overall structure changes from a "needle-shaped cluster" to a "petal cluster".

[0083] in addition, Figures 1 to 3 The particle size distribution in Figure 2 shows that the widths of MOF@CNCs-1, MOF@CNCs-2, and MOF@CNCs-3 are 0.61, 1.2, and 4.8 μm, respectively, and the corresponding lengths are approximately 50.1, 95.8, and 134.4 μm. This change in size parameters indicates that the aspect ratio of the MOF@CNCs composites decreases with increasing CNCs content.

[0084] Comparative Example 1

[0085] Dissolve 30 mg Zn(CH3COO)2 in 3 mL of DEF to obtain a Zn(CH3COO)2 solution;

[0086] Dissolve 10 mg of H4TCPE in 3 mL of ethanol to obtain a H4TCPE solution;

[0087] Under magnetic stirring, the H4TCPE solution was added dropwise to the Zn(CH3COO)2 solution, and then 40 μL of 98 wt.% nitric acid was added, and stirred at 800 rpm for 10 min, followed by heating at 80 ° C for 48 h. The solid phase obtained by the reaction was washed alternately with anhydrous ethanol and ultrapure water to neutrality to obtain pure MOF.

[0088] Detection:

[0089] 1. Lactic acid fluorescence detection of MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3:

[0090] MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3 were mixed with appropriate amounts of water to obtain aqueous suspensions of MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3 with a concentration of 14 mg / L.

[0091] The microfluorescence images of MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3 under 365 nm laser irradiation are shown in Figure 2. Figure 4 a~c, from Figure 4 It can be seen that the aqueous suspensions of MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3 all show blue-green fluorescence emission.

[0092] 2. Standard curve:

[0093] In order to simulate the test of lactic acid in human sweat, the present invention evenly disperses MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3 in PBS buffer and tests the standard curve, specifically, including the following steps:

[0094] (1) MOF@CNCs-1, MOF@CNCs-2 and MOF@CNCs-3 were uniformly dispersed in PBS buffer (pH = 5.5) to obtain a MOF@CNCs-1 suspension with a concentration of 14 mg / L, a MOF@CNCs-2 suspension with a concentration of 14 mg / L and a MOF@CNCs-3 suspension with a concentration of 14 mg / L, respectively;

[0095] (2) The initial fluorescence intensity F0 of MOF@CNCs-1 suspension, MOF@CNCs-2 suspension and MOF@CNCs-3 suspension was tested respectively. When testing the initial fluorescence intensity, the excitation wavelength was 365 nm.

[0096] (3) Add a series of concentrations of lactic acid standard solution (5 mM, 10 mM, 20 mM, 30 mM, 40 mM, 50 mM, 60 mM, and 70 mM) into the MOF@CNCs-1 suspension, MOF@CNCs-2 suspension, and MOF@CNCs-3 suspension, respectively.

[0097] (4) The fluorescence intensity F of MOF@CNCs-1 suspension, MOF@CNCs-2 suspension and MOF@CNCs-3 suspension with different concentrations was tested respectively. During the test, the excitation wavelength was 365 nm.

[0098] (5) According to the fluorescence intensity F, the initial fluorescence intensity F0 and the concentration of lactic acid in the suspension, a linear fit is performed with the concentration of lactic acid in the suspension as the abscissa and the logarithm of F / F0 as the ordinate to obtain a predetermined standard curve. Figure 5 Among them, when the linear range is 0-70mM, the predetermined standard curve of MOF@CNCs-1 is: Ln(F / F0)=0.034C LA +0.77(R 2 =0.998); the predetermined standard curve of MOF@CNCs-2 is: Ln(F / F0)=0.029C LA +0.80(R 2 =0.991); the predetermined standard curve of MOF@CNCs-3 is: Ln(F / F0)=0.028C LA +0.4(R 2 =0.993), with a detection limit of 62.7 nM.

[0099] 3. Taking MOF@CNCs-1 as an example, Figure 6 (a) is an optical image of the MOF@CNCs-1 suspension after adding different concentrations of lactic acid solution to the MOF@CNCs-1 suspension under 365nm ultraviolet light excitation; Figure 6 (b) is the CIE chromaticity diagram of MOF@CNCs-1 suspension when the lactic acid concentration ranges from 0 to 70 mM. Figure 6 As can be seen from (a) and (b), under ultraviolet irradiation of 365 nm, at different lactic acid concentrations, the photoluminescence behavior of MOF@CNCs transitions from light blue at 0 mM to bright blue-green at 70 mM, and the chromaticity coordinates change from (0.167, 0.196) to (0.213, 0.398).

[0100] 4. Test the unknown concentration of lactic acid solution

[0101] Add the lactic acid solution of unknown concentration to the 14 mg / L MOF@CNCs-1 suspension to obtain the test solution;

[0102] The fluorescence intensity F of the test liquid is tested. When testing the fluorescence intensity, the excitation wavelength is 365 nm;

[0103] Substituting F into the predetermined standard curve of MOF@CNCs-1, the concentration of lactic acid in the suspension was obtained to be 32.5 mM.

[0104] The present invention also conducts a sensing detection test on MOF@CNCs-1 and the pure MOF prepared in the comparative example. The test steps are as follows: MOF@CNCs-1 and MOF are uniformly dispersed in PBS buffer (pH=5.5) to obtain a MOF@CNCs-1 suspension and a MOF suspension with a concentration of 14 mg / L, respectively; a series of concentrations of lactic acid standard solutions are added to the MOF@CNCs-1 suspension and the MOF suspension, respectively (so that the lactic acid concentration in the mixed solution after adding lactic acid is 5 mM, 10 mM, 20 mM, 30 mM, 40 mM, 50 mM, 60 mM, and 70 mM, respectively); the fluorescence intensities of the MOF@CNCs-1 and lactic acid mixed solutions and the MOF and lactic acid mixed solutions containing different concentrations of lactic acid are tested, respectively, and the excitation wavelength during the test is 365 nm. The concentration of lactic acid in the suspension was taken as the horizontal axis, and the logarithm of the ratio of the fluorescence intensity of the test solution to the initial fluorescence intensity was taken as the vertical axis. A linear fit was performed. The experimental results are shown in Figure 7 ,from Figure 7 It can be seen that the sensing performance of MOF@CNCs-1 is more sensitive.

[0105] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a fluorescent metal organic framework / cellulose nanocrystal composite material, characterized in that: The following steps are involved: A zinc acetate solution, a tetra(4-carboxyphenyl)ethylene solution, nitric acid and a CNCs suspension are mixed and subjected to a solvothermal reaction to obtain a fluorescent metal organic framework / cellulose nanocrystal composite material; The mass ratio of zinc acetate to tetra(4-carboxyphenyl)ethylene to CNCs is (10-100):(5-100); The mass ratio of tetra(4-carboxystyrene)ethylene to CNCs is (5-20):(0.1-5).

2. The preparation method according to claim 1, characterized in that The concentration of the CNCs suspension is 1 to 10 wt.%.

3. The preparation method according to claim 1, characterized in that: The mass ratio of zinc acetate to the volume ratio of the solvent in the zinc acetate solution is (10-100) mg: (1-15) mL; the mass ratio of tetra(4-carboxyphenyl)ethylene to the volume ratio of the solvent in the tetra(4-carboxyphenyl)ethylene solution is (5-100) mg: (1-15) mL.

4. The preparation method according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 50-120° C., and the insulation time is 12-72 hours.

5. The fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The aspect ratio of the fluorescent metal organic framework / cellulose nanocrystal composite material is (15-100):1; the fluorescent metal organic framework / cellulose nanocrystal composite material comprises cellulose nanocrystals and MOF supported on the cellulose nanocrystals; the metal atom of the MOF is Zn, and the ligand is tetra(4-carboxyphenyl)ethylene.

6. The fluorescent metal organic framework / cellulose nanocrystal composite material as claimed in claim 5, wherein the morphology of the fluorescent metal organic framework / cellulose nanocrystal composite material is "needle-like clusters" or "petal clusters".

7. Use of the fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the preparation method according to any one of claims 1 to 4 or the fluorescent metal organic framework / cellulose nanocrystal composite material according to any one of claims 5 to 6 in detecting lactic acid.

8. A method for detecting lactic acid using the fluorescent metal organic framework / cellulose nanocrystal composite material according to claim 5 or 6, characterized in that: The following steps are involved: Test the initial fluorescence intensity F0 of the fluorescent metal organic framework / cellulose nanocrystal composite solution; After mixing the test solution containing lactic acid and the fluorescent metal organic framework / cellulose nanocrystal composite material solution, the fluorescence intensity is tested to obtain the fluorescence intensity F of the test solution; Obtaining the concentration of lactic acid in the test solution containing lactic acid according to a predetermined linear curve, the initial fluorescence intensity F0 and the ratio F / F0 of the fluorescence intensity F; The predetermined linear curve is F 标准 Linear relationship curve between / F0 and lactate concentration; The F 标准 To test the fluorescence intensity of fluorescent metal organic framework / cellulose nanocrystal composite solutions containing different concentrations of lactic acid.

9. A paper sensor, characterized in that: The invention comprises a paper substrate and a fluorescent metal organic framework / cellulose nanocrystal composite material loaded in the paper substrate; the fluorescent metal organic framework / cellulose nanocrystal composite material is a fluorescent metal organic framework / cellulose nanocrystal composite material prepared by the preparation method described in any one of claims 1 to 4 or a fluorescent metal organic framework / cellulose nanocrystal composite material described in any one of claims 5 to 6.

10. The paper sensor according to claim 9, characterized in that The fluorescent metal organic framework / cellulose nanocrystal composite material is relatively 2 The loading capacity of the paper matrix is ​​5×10 -6 ~1×10 -3 mg.

Citation Information

Patent Citations

  • Bio-based porous material and preparation method and application thereof

    CN113861600A

  • Hydrogel film for pollutant removal and fluorescence detection in water body and preparation method of hydrogel film

    CN117304528A

  • Metal organic framework polymer mixed matrix membranes

    US20110138999A1